Identifying patients with shoulder impingement syndrome who improve with scapular training: a clinical prediction study - El Melhat, Ahmed M.; Khater Mohamed, Hager Tarek; Youssef, Enas Fawzy; Gad, Ahmed Mahmoud; Ali Al Hamaky, Dina Mohamed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. There is a preponderance of evidence that scapular training improves scapular muscle performance and decreases the clinical symptoms related to subacromial impingement syndrome (SAIS). To investigate if pain severity, functional disability, scapular upward rotation angle, and upper trapezius/serratus anterior (UT/SA) isometric strength ratio at baseline assessment can predict a patient’s response to scapular training in cases of SAIS.Methods. A clinical predictive study was performed on forty-ﬁve patients, suﬀering from SAIS, the assessment included pain severity, disability assessment, scapular upward rotation, and the UT/SA isometric strength ratio. Measurements were collected before and after a 4-week intervention program of scapular muscle training and strengthening of the serratus anterior muscle. The sensitivity and speciﬁcity of interfering with this procedure were utilized to identify items included in the clinical prediction rule (CPR).Results. Excellent results were shown by the area under the receiver operating characteristic curve (ROC curve) with a pain severity of 0.93 (sensitivity 0.9, speciﬁcity 0.33), functional disability of 0.94 (sensitivity 0.956, speciﬁcity 0.156), and UT/SA iso-metric strength ratio of 0.9 (sensitivity 0.9, speciﬁcity 0.33) and poor results with a scapular upward rotation angle of 0.66 (sensi-tivity 0.62, speciﬁcity 0.36) as static positioning of the scapula was believed not to be adequate in assessing prediction values, and with the upward scapular rotation angle recently being highlighted as not aﬀecting symptoms of SAIS.Conclusions. This study revealed that shoulder pain, functional disability, and UT/SA isometric strength ratios potentially serve as predictors of the eﬃcacy of a scapular training program in patients who suﬀer from SAIS.
Keywords: clinical prediction; musculoskeletal; rehabilitation; rotator cuﬀ; scapular training; shoulder pain